2017
DOI: 10.1016/j.jfda.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial phenolic compounds from extracts of cultivated and wild-grown Tunisian Ruta chalepensis

Abstract: The antioxidant and antibacterial activities of phenolic compounds from cultivated and wild Tunisian Ruta chalepensis L. leaves, stems, and flowers were assessed. The leaves and the flowers exhibited high but similar total polyphenol, flavonoid, and tannin content. Moreover, two organs showed strong, although not significantly different, total antioxidant activity, 2,2-diphenyl-1-picrylhydrazyl scavenging ability, and reducing power. Investigation of the phenolic composition showed that vanillic acid and couma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 25 publications
5
59
1
Order By: Relevance
“…Other different results were obtained by Fan, Yuan, Wang, Gao, and Huang () in the case of A. officinalis who identified five antioxidant compounds, namely ferulic acid, kaempferol, quercetin, rutin, and isorhamnetin. Our results corroborated those of Ouerghemmi et al () who found high proportion of vanillic acid compound in Ruta chalepensis leaf extract. This later showed a strong antioxidant and antimicrobial activities.…”
Section: Discussionsupporting
confidence: 93%
“…Other different results were obtained by Fan, Yuan, Wang, Gao, and Huang () in the case of A. officinalis who identified five antioxidant compounds, namely ferulic acid, kaempferol, quercetin, rutin, and isorhamnetin. Our results corroborated those of Ouerghemmi et al () who found high proportion of vanillic acid compound in Ruta chalepensis leaf extract. This later showed a strong antioxidant and antimicrobial activities.…”
Section: Discussionsupporting
confidence: 93%
“…Free caffeic (CA) acid is also found in SFM but accounts for just 0.5 % of the TPC content (Guo et al, 2017;Szydłowska-Czerniak et al, 2011;Weisz et al, 2009). Phenolic acids, particularly hydroxycinnamic acids, are bioactive molecules with interesting properties that include antioxidant (Gullón et al, 2018;Shahidi and Ambigaipalan, 2015), anti-inflammatory (Oueslati et al, 2012) and antimicrobial (Ouerghemmi et al, 2017) activities among others. These bioactive properties can be enhanced by modifying the hydrophilic/hydrophobic balance of the molecules (Laguerre et al, 2013;Lecomte et al, 2010;Szydłowska-Czerniak et al, 2018).…”
mentioning
confidence: 99%
“…Antioxidants are compounds that can delay or inhibit the oxidation of lipids or other molecules by inhibiting the initiation or propagation of oxidizing chain reactions (Volf et al, 2013). Nowadays, antioxidant agents of natural origin have attracted special interest because they can protect the human body from free radicals, due to its high content of polyphenolic compounds (Pandey & Rizvi, 2009). Accordingly, antioxidants can protect the body from reactive oxygen species (ROS) that damages cells and prevent carcinogenesis by scavenging them.…”
Section: Ruta Chalepensis L In Jordanmentioning
confidence: 99%
“…Plants such as Ruta chalepensis L. are considered a valuable source of bioactive components such as natural antioxidants which possess defense mechanism against ROS (Ouerghemmi et al, 2017;Romojaro, Botella, Obón, & Pretel, 2013). Polyphenols constitute the main bioactive phytochemicals that have been proven effective in the prevention of certain chronic diseases such as coronary heart diseases, cancers and diabetes due to their free radical-scavenging activities (Lamien-Meda et al, 2008).…”
Section: Lipid Peroxidation (Mda) Assaymentioning
confidence: 99%